Assessment of the impact of foreign direct Investment on economic growth in Tanzania: Evidence from the manufacturing sector - Kabigiza, Dorica (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for award of Master of Business Administration Corporate Management (MBA- CM) of Mzumbe University